The diameter-dependent photoelectrochemical performance of silicon nanowires. Issue 7 (30th November 2015) - Zhang, Bing-Chang; Wang, Hui; He, Le; Duan, Chun-Yang; Li, Fan; Ou, Xue-Mei; Sun, Bao-Quan; Zhang, Xiao-Hong
Abstract : We demonstrate the first systematic study of the diameter-dependent photoelectrochemical performance of single silicon nanowires within a broad size range from 200 to 2000 nm. Abstract : We demonstrate the first systematic study of the diameter-dependent photoelectrochemical performance of single silicon nanowires within a broad size range from 200 to 2000 nm. SiNWs with a diameter of 1415 nm exhibit the highest solar energy conversion efficiency, which can be mainly traced to their diameter-dependent light absorption properties.